Long COVID and episodic disability: advancing the conceptualisation, measurement and knowledge of episodic disability among people living with Long COVID – protocol for a mixed-methods study. Issue 3 (7th March 2022) - O'Brien, Kelly K; Brown, Darren A; Bergin, Colm; Erlandson, Kristine M; Vera, Jaime H; Avery, Lisa; Carusone, Soo Chan; Cheung, Angela M; Goulding, Susie; Harding, Richard; McCorkell, Lisa; O'Hara, Margaret; et al.
Abstract : Introduction: As the prevalence of Long COVID increases, there is a critical need for a comprehensive assessment of disability. Our aims are to: (1) characterise disability experiences among people living with Long COVID in Canada, UK, USA and Ireland; and (2) develop a patient-reported outcome measure to assess the presence, severity and episodic nature of disability with Long COVID. Methods and analysis: In phase 1, we will conduct semistructured interviews with adults living with Long COVID to explore experiences of disability (dimensions, uncertainty, trajectories, influencing contextual factors) and establish an episodic disability (ED) framework in the context of Long COVID (n 10 each country). Using the conceptual framework, we will establish the Long COVID Episodic Disability Questionnaire (EDQ). In phase 2, we will examine the validity (construct, structural) and reliability (internal consistency, test–retest) of the EDQ for use in Long COVID. We will electronically administer the EDQ and four health status criterion measures with adults living with Long COVID, and readminister the EDQ 1 week later (n 170 each country). We will use Rasch analysis to refine the EDQ, and confirm structural and cross-cultural validity. We will calculate Cronbach's alphas (internal consistency reliability), and intraclass correlation coefficients (test–retest reliability), and examine correlations for hypotheses theorising relationships between EDQ and criterion measure scores (construct validity). Using phase 2 data, we will characterise the profile of disability using structural equation modelling techniques to examine relationships between dimensions of disability and the influence of intrinsic and extrinsic contextual factors. This research involves an academic–clinical–community partnership building on foundational work in ED measurement, Long COVID and rehabilitation. Ethics and dissemination: This study was approved by the University of Toronto Research Ethics Board. Knowledge translation will occur with community collaborators in the form of presentations and publications in open access peer-reviewed journals and presentations.